Model MBKM Kelas Menulis Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung - Fitriani Fitriani; Susanti Vera; Hidayatul Fikra (UIN Sunan Gunung Djati Bandung, 2024)
This research aims to explain the model of the independent campus learning (MBKM) through Writing Classes. This research uses a qualitative approach by applying the policy review method. The results and discussion of this research include the name of the activity, objective of the activity, general provisions, requirements, course conversion package, registration procedures, variety of generic courses, quality assurance, implementation schedule, financing, and organizers. This research concludes that the model of the independent campus learning (BMKM) through the Writing Class is a solution for students' rights in subject conversion.